Zakat and Youth Empowerment - Risa Sari Pertiwi; Sri Herianingrum; Aditya Kusuma (Center of Strategic Studies (PUSKAS) BAZNAS, 2020)
Unemployment in Indonesia is currently dominated by young people. Zakat as one of the Islamic social finance instruments which has a crucial impact in the socio-economic development of a country. The aim of this research is to explore the relationship between zakat institution support, the successful of youth empowerment program, and individual welfare by Al-Azhar Zakat Institution. This paper also develops a model for the youth empowerment programs that will have an impact on the individual welfare mustahik based on Maqashid Sharia indicators and mustahik social welfare. This study uses primary data with purposive sampling and uses quantitative approach a path model. The main finding of this research showed that success of youth empowerment program fully significant mediated the relationship between zakat institution support and individual welfare. The study contributes to the existing literatures and managerial implications for zakat institution in developing a youth empowerment model to increase social prosperity.